Land subsidence at aquaculture facilities in the Yellow River delta, China. Issue 15 (6th August 2013) - Higgins, Stephanie; Overeem, Irina; Tanaka, Akiko; Syvitski, James P. M.
<x xml:space="preserve">Abstract</x> [1] Differential Interferometric Synthetic Aperture Radar is applied to the coast of the Yellow River delta (YRD) in China. Like many deltas, the coastline of the YRD is dominated by aquaculture. Advanced Land Observation Satellite Phased Array L‐Band Synthetic Aperture Radar (SAR) and Envisat Advanced SAR data acquired between 2007 and 2011 show that subsidence rates are as high as 250 mm/y at aquaculture facilities, likely due to groundwater pumping. These rates exceed local and global average sea level rise by nearly 2 orders of magnitude and suggest that subsidence and associated relative sea level rise may present a significant hazard for Asian megadeltas.